The moderating effect of understanding advertising intent on the relation between advertising recognition and problematic use of loot boxes among minors: An exploratory study - Joaquín González-Cabrera; Vanessa Caba-Machado; Beatriz Feijóo; Adoración Díaz-López; Raquel Escortell; Juan Manuel Machimbarrena (Acta Psychologica, 2024)
The use of loot boxes has been compared to gambling due to its random nature, with the consequent risk of being conceived as an ordinary activity implemented in the daily routine. One of the factors contributing to these gambling behaviors is exposure to gambling advertisements. It is essential to protect children and adolescents from prejudicial advertising, since due to their psycho-evolutionary development, advertising makes them impressionable and suggestible. Currently, there is scarcely any research on the influence of advertising on underage buyers of loot boxes. Knowledge in this regard is important to adequately address efforts to protect minors from the potential impact of gambling and its advertising. Thus, this study aims to examine how understanding advertising intent in loot box advertising moderates the relationship between the recognition of loot box advertising and the problematic usage of loot boxes in a sample of adolescents. The present study used a cross-sectional design, and the sample is composed by 451 adolescents (85.8 % male) that played videogames and purchased loot boxes in the last 12 months. Results indicated that understanding advertising intent played a moderating role in the relationship between advertising recognition and Problematic Use of Loot Boxes, strengthening it positively. The findings showed that when there was a low degree of understanding advertising intent, the former relationship was not significant. However, with a high level of understanding advertising intent the relationship between advertising recognition and Problematic Use of Loot Boxes was significant and strengthened. This means that knowing how ads try persuading the player affects how adverts are linked to PULB. Specifically, if adolescents understand that ads are trying to sell them loot boxes, this knowledge makes the relationship between seeing ads and having PULB stronger. These results are of interest for advertising literacy strategies.